Silicon Drift Detectors for the Measurement and Reconstruction of Beta Spectra - Andrea Nava; Leonardo Bernardini; Matteo Biassoni; Tommaso Bradanini; Marco Carminati; Giovanni De Gregorio; Carlo Fiorini; Giulio Gagliardi; Peter Lechner; Riccardo Mancino; Chiara Brofferio (Sensors)
The ASPECT-BET project, or An sdd-SPECTrometer for BETa decay studies, aims to develop a novel technique for the precise measurement of forbidden beta spectra in the 10 keV–1 MeV range. This technique employs a Silicon Drift Detector (SDD) as the main spectrometer with the option of a veto system to reject events exhibiting only partial energy deposition in the SDD. A precise understanding of the spectrometer’s response to electrons is crucial for accurately reconstructing the theoretical shape of the beta spectrum. To compute this response, GEANT4 simulations optimized for low-energy electron interactions are used and validated with a custom-made electron gun. In this article we present the performance of these simulations in reconstructing the electron spectra measured with SDDs of a 109Cd monochromatic source, both in vacuum and in air. The allowed beta spectrum of a 14C source was also measured and analyzed, proving that this system is suitable for the application in ASPECT-BET.